2006
DOI: 10.1088/0963-0252/16/1/018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-induced ignition and plasma-assisted combustion in high-speed flow

Abstract: The suitability of the electrical discharge technique for application in plasma-induced ignition and plasma-assisted combustion in high-speed flow is reviewed. Nonequilibrium, unsteady and nonuniform modes are under analysis to demonstrate the advantage of such a technique over heating. A reduction in the required power deposition is possible due to unsteady operation and non-homogeneous spatial distribution. Mixing intensification in non-premixed flow could be achieved by nonuniform electrical discharges. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 13 publications
(22 reference statements)
0
50
0
Order By: Relevance
“…A driving force is the demand to avoid global warming due to the greenhouse effect since more than 80% of fossil fuels are consumed by combustion. Recently, plasmaassisted combustion has been investigated as an innovative technology [1], which is expected to be useful for combustion in a lean-fuel condition [2,3] and in a speedy flow [4][5][6]. In addition, it is considered that plasmas can be utilized for improving the ignition characteristics [7][8][9][10][11] and the stability of flames [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A driving force is the demand to avoid global warming due to the greenhouse effect since more than 80% of fossil fuels are consumed by combustion. Recently, plasmaassisted combustion has been investigated as an innovative technology [1], which is expected to be useful for combustion in a lean-fuel condition [2,3] and in a speedy flow [4][5][6]. In addition, it is considered that plasmas can be utilized for improving the ignition characteristics [7][8][9][10][11] and the stability of flames [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence flow has been neglected. 6. Although the light absorption can occur in the actual ICTP, this can be omitted as optically thin plasma has been assumed.…”
Section: Hypothesismentioning
confidence: 99%
“…In addition, for the last couple of decades researchers have shown particular interests in applications of non-equilibrium plasma for the problems of plasma assisted ignition and plasma assisted combustion of hydrocarbon fuels [6,7] due to the fact that an electrical discharge's properties strongly depend on the conditions of excitation of discharge, flow parameters and characteristics of supplying electromagnetic power. It has been reported that, by using plasma assistance, the combustion rate can be enhanced, thereby greatly reducing the combustion temperature [8].…”
mentioning
confidence: 99%
“…The method of optical spectroscopy is used to measure plasma temperature [18], [19]. Measurements were carried out in the separation zone of the duct at three different values of the mean discharge current: I pl = 16, 10, and 6.5 A.…”
Section: Measurements Of Plasma Temperaturementioning
confidence: 99%